PWE-096 The Impact Of Surgeon Specific Outcome Data On Patient Choice. (9th June 2014) - Harris, R; Mayberry, J
Abstract : Introduction: Patients have a legal right to choose their own treatment and care within the modern NHS 1 . NHS England and the Association of Coloproctology of Great Britain and Ireland 2, has recently released the mortality rates for individual colorectal surgeons for patients within the first 90 days of a planned operation undertaken for bowel cancer. With these figures now publicly accessible on the Internet, Gastroenterology physicians, in collaboration with their inflammatory bowel disease (IBD) patients, could utilise the information to assist in deciding who they would choose to perform the surgery should it be required. Methods: One hundred and ten consecutive IBD patients who had stable disease, and seen within the outpatient setting, completed a questionnaire about which fictional surgeon they would choose dependent on the published mortality rates and their location within the country. The options included a fictional surgeon with the lowest mortality rate who was based furthest away (Newcastle), a fictional surgeon with the highest mortality rate who was local (Leicester) and a fictional surgeon with an average mortality rate who was based in between (Nottingham). There was an additional option of the patient allowing their fictional gastroenterologist to decide for them. Similarly, ten Gastroenterology colleagues were also questioned about this surgeon-specific outcome data. Results: The majority of the 110 IBD patients chose between two options. 45% chose a fictional surgeon with the lowest mortality rate based furthest away (Newcastle) and 41% opted for their fictional Gastroenterology consultant to decide for them. Of the 10 Gastroenterology colleagues questioned 50% were aware that the information was now publicly accessible, 20% were aware of where to access the information and 10% had reviewed the information online. On answering which fictional surgeon they would choose if the patient wanted their Gastroenterologist to decide for them, 40% chose the fictional surgeon with the lowest mortality rates based furthest away (Newcastle) and 20% chose the fictional surgeon with the highest mortality rates based locally (Leicester). Conclusion: The Government has proposed that the NHS allows patients to make informed choices about their own care. These results demonstrate that given that choice these IBD patients would either choose a surgeon with the lowest mortality rates, even if they were not based locally, or would allow their own Gastroenterologist to decide for them. However, the majority of the Gastroenterologists surveyed had not utilised the information on surgeon-specific outcomes. The legal consequences for gastroenterologists who choose the "less than best" option are yet to be tested in court. References: 2013/2014 Choice Framework, NHS England Individual surgical outcomes for England 2013, The Association of Coloproctology of Great Britain and Ireland Disclosure of Interest: None Declared.